Relatuhedron: a machine of possibilities - Rodriguez Camacho, Juan Carlos (Springer, 2022)
A journey of new routes of healing with/by Indigenous and non-Indigenous participants is shared under the Two Eyed-Seeing Perspective of Elder Albert Marshall. The Universal Human Right of Indigenous self-determination and Relationality are the togetherness presented in a "mangrove tree" that lives between salty and sweet waters emerging as a protective place of rich ecosystems. The relatuhedron (shapes of relationality) a co-construction of a home, a Wigwam, Long House, Maloca, Ue, crystalizes knowledge and practices in the process of individual and community healing and cultural transactions. A set of neologisms such as relatuhedron, pedagomiologies, and social grammars, is proposed to challenge our views of mental health, healing, cultural transactions, stereotypes, recovery, and public policy and include simplicities and complexities required to support Indigenous well-being. It is a "machine of possibilities" for students and professionals working with/by and for Indigenous communities. In this book healing is presented as a process through scholarly practice and reflection. Healing is a process of emergence of meaning by improving relationality with the self, nature and others, in a practical approach to socio-cultural transformations. In sum, healing is based on individual and community processes both honoring and respective Indigenous knowledge and scientific research to create endless opportunities for well-being. This book presents healing as a process of growth, a complex, dynamic and evolutive journey of transforming how we stablish and maintain relationships with the self, nature and others inside of our cultural negotiations